Clinical Efficacy of Gauze Tamponade in Preventing Vaginal Bleeding After Transvaginal Oocyte Retrieval: A Retrospective Analysis - Wei Q; Wang X; Yang X; He Y; Hong X; Wang Z (International Journal of Women's Health)
Qun Wei, Xiufen Wang, Xinyi Yang, Yu He, Xia Hong, Zilian Wang Nursing Department, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Hangzhou City, Zhejiang Province, People’s Republic of ChinaCorrespondence: Zilian Wang, Email yanchen517@126.comObjective: To evaluate the clinical value of routinely using sterile gauze strips to occlude the vagina after transvaginal ultrasound-guided oocyte retrieval (TVOR) in preventing postoperative vaginal bleeding.Methods: The medical records of 1194 patients who underwent transvaginal oocyte retrieval between March and April 2024 were retrospectively analyzed. Patients with no obvious bleeding at the vaginal puncture site were divided into group A (without gauze packing, 586 cases) and group B (with conventional gauze packing, 608 cases) according to whether gauze was used to control bleeding. The incidence of vaginal bleeding at 30 minutes, 1 hour, 3 hours and bloody discharge at 3 days after oocyte retrieval was compared by the chi-square test between the two groups. Patients in group B were also assessed for their tolerance of gauze tamponade removal and the ease and accuracy of postoperative gauze management.Results: There was no statistical difference in general patient information between the two groups (P> 0.05). Compared with group B the incidence of vaginal bleeding at 30 minutes (χ2=8.631, P< 0.05) and the incidence of bloody or brown vaginal discharge 3 days (χ2=56.50, P< 0.05) postoperatively was significantly higher in group A, and the incidence of vaginal bleeding at 1 hour postoperatively and 3 hours postoperatively was not significantly different in the two groups (P> 0.05). Patients in group B tolerated vaginal tamponade and gauze removal better.Conclusion: Routine use of sterile gauze after transvaginal oocyte collection significantly reduces the incidence of vaginal bleeding and is well tolerated by patients.Keywords: transvaginal oocyte retrieval, complications, vaginal bleeding, gauze tampon insertion, retrospective study